2022
DOI: 10.1071/ma22039
|View full text |Cite
|
Sign up to set email alerts
|

Strong relationships between the Northern Territory of Australia and Timor-Leste

Abstract: Strong, enduring partnerships exist between the Northern Territory and Timor-Leste, and in recent years collaborations have led to significant developments in health system capacity in Timor-Leste. Laboratory strengthening has been a key focus; improved diagnostic microbiology capability, especially in the National Health Laboratory, is having an impact on individual patient management and outcomes, epidemiological surveillance, and public health responses to communicable disease challenges including antimicro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

6
0

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 9 publications
(12 reference statements)
0
11
0
Order By: Relevance
“…The Fleming Fund Grant (UKAid) investment at the NHL by Menzies provided the foundation for more microbiological work, including capacity building, research and surveillance. 24 The expansion of NHL-MDL directly benefits microbiology (AMR) work, where GeneXpert platforms are utilised for detecting resistant genes, including a recently detected Acinetobacter baumannii carrying New Delhi metallo-β-lactamase 1 (NDM-1) gene. 25 …”
Section: Discussionmentioning
confidence: 99%
“…The Fleming Fund Grant (UKAid) investment at the NHL by Menzies provided the foundation for more microbiological work, including capacity building, research and surveillance. 24 The expansion of NHL-MDL directly benefits microbiology (AMR) work, where GeneXpert platforms are utilised for detecting resistant genes, including a recently detected Acinetobacter baumannii carrying New Delhi metallo-β-lactamase 1 (NDM-1) gene. 25 …”
Section: Discussionmentioning
confidence: 99%
“…The Korea International Cooperation Agency contributed significantly to strengthening tuberculosis diagnostic capacity, including for PCR testing 12. Other investments were supported by the Australian Government’s Indo-Pacific Centre for Health Security and the United Kingdom’s Fleming Fund, focused on diagnostic microbiology for infectious diseases testing and surveillance 7 9 13…”
Section: The Importance Of Preparedness For Health Emergenciesmentioning
confidence: 99%
“… 12 Other investments were supported by the Australian Government’s Indo-Pacific Centre for Health Security and the United Kingdom’s Fleming Fund, focused on diagnostic microbiology for infectious diseases testing and surveillance. 7 9 13 …”
Section: The Importance Of Preparedness For Health Emergenciesmentioning
confidence: 99%
“…Timor-Leste is a half-island nation located between Indonesia and Australia with a population of 1.3 million. Despite significant recent improvements in diagnostic laboratory and infectious disease surveillance capacity, including the implementation of bacterial culture and molecular diagnostic platforms for SARS-CoV-2 and tuberculosis at multiple sites across the country, there have been no prospective studies of AFI in Timor-Leste [20 , 21] . In 2008-2010, a retrospective review of pediatric hospitalizations at the Hospital Nacional Guido Valadares (HNGV), Dili found that AFI was the most common reason for admission; however, only limited etiological, treatment-related and outcome data were available in this study [22] .…”
Section: Introductionmentioning
confidence: 99%